Trade practices of retail chains as far as the transaction cost analysis in relationships manufacturer – retailer are concerned - Kita, Jaroslav; Máziková, Katarína; Grossmanová, Marta; Kita, Pavol (Business: Theory and Practice, 2012)
Paper is based on the knowledge of the theory of transaction cost analysis, which makes it possible for the members of the distribution channel to make decisions on the number of forms of the organization in order to realize their activities successfully. That explains the functioning of the relations on the basis of the transaction costs theory and helps understand how the retail chain makes its decisions with the aim of lowering the costs resulting from its activity with regard to its own strategic goals in the context of cooperation with the milk producer. In this framework and using the example of milk, the article shows the trade practices of retail chains to improve the relationships manufacturer – retailer in the Slovak consumer market.